Вовка Абрамушкин, Вася Белкин и другие такие же - Георгиев Сергей Георгиевич (Класс!ные истории, 2008)
Экземпляры: ф. 1 (20090206) / Инвентарный номер: 93545 / Цена: 119.80 / Авт.знак: Г 36 / ГРНТИ: 17.82 / ББК: 84(2=411.2)6